Implementation of Bandura's Social Learning Theory in Community-Based Non-Formal Islamic Religious Education: A Case Study of Religious Learning Activities at Majelis Nurul Hidayah, Barito Kuala Regency - Andri Suryani; Mazrur (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study examines the implementation of Albert Bandura’s Social Learning Theory in community-based non-formal Islamic Religious Education through religious lecture activities at Majelis Nurul Hidayah, Rangga Surya Village, Barito Kuala Regency. While previous studies have predominantly explored Social Learning Theory within formal educational settings, limited attention has been given to its application in community-based religious learning environments. This study addresses this gap by investigating how social learning processes contribute to the development of congregants’ religious character in a non-formal Islamic education context. A descriptive qualitative approach was employed. Data were collected through participant observation, semi-structured interviews, and documentation. The participants consisted of a preacher, administrators of the religious assembly, and congregation members who regularly attended religious lecture activities involving approximately 300 participants. Data were analyzed using data reduction, data display, and conclusion drawing techniques, supported by source and method triangulation to ensure credibility. The findings indicate that social learning occurs through observational learning, modeling, social interaction, and reinforcement. The preacher’s exemplary conduct functions as a primary learning model, while interactive discussions and positive reinforcement encourage participants’ engagement and value internalization. The study further reveals that participants demonstrated enhanced religious understanding and reported behavioral changes related to honesty, discipline, responsibility, and social conduct. The novelty of this study lies in extending Bandura’s Social Learning Theory to a community-based non-formal Islamic education setting and demonstrating how social learning mechanisms collectively contribute to religious character formation among adult congregants. The findings contribute theoretically to the development of Social Learning Theory in Islamic education and practically provide insights for designing more effective community-based religious learning programs.